CORRELATION DEPENDENCE OF THE USE OF GENERAL AND SPECIAL-PREPARATORY (BOXING EQUIPMENT) EXERCISES AND PSYCHOPHYSIOLOGICAL INDICATORS AND THE LEVEL OF MANIFESTATION OF THE STRENGTH OF PUNCHES BY YOUNG BOXERS OF 15-16 YEARS OLD - Yuri Shestak; Viacheslav Mulyk (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to establish a correlation relationship between general and special preparatory exercises and strength indicators of punches with hands, as well as psychophysiological qualities that arise during training. Material and methods: the research was carried out with the involvement of young boxers 15-16 years old, who made up an experimental group in the amount of 12 athletes, they carried out a one-cycle annual training process according to the CYSS program at the beginning of the preparatory period (control testing was carried out after the retractive mesocycle), and at the end of the competitive period repeated testing was carried out using the means of general and special physical training and psychophysiological indicators. The above made it possible to establish a correlation dependence between the indicated indicators. Results: the results obtained allow, when building a training process aimed at increasing the absolute and relative strength of a punch in boxing, to take into account the effectiveness of using general and special preparatory exercises in relation to the main punching movements of boxers. Conclusions: the results obtained make it possible to more effectively plan the training process with the use of general and special-preparatory exercises for solving problems of the development of speed-strength qualities, which are the basis of the absolute and relative strength of the punch in boxing.